Synthesis of Polyhydroquinolines Hantzsch Reaction Catalyzed by Starch Sulfuric Acid in Water - WU, HUI; CHEN, XIU-MEI; WAN, YU; XIN, HAI-QIANG; LIAN, SHU-QIN; YE, LING (Asian Journal of Chemistry, 2010)
Starch sulfuric acid was used as efficient catalyst of 4-components Hantzsch reaction of various aromatic aldehydes, dimedone, ammonium acetate and ethyl acetoatetate or acetylacetone in water at room temperature to afford polyhydroquinolines in high yields. The process is operationally simple, environmentally friendly and rapid. Furthermore, the catalyst is obtained easily and cheaply.